Money demand in general equilibrium endogenous growth: Estimating the role of a variable interest elasticity - Max Gillman; Glen Otto (Cardiff University, Cardiff Business School, 2006)
The paper presents and tests a theory of the demand for money that is derived from a general equilibrium, endogenous growth economy, which in eect combines a special case of the shopping time exchange economy with the cash-in-advance framework. The model predicts that both higher ináation and Önancial innovation - that reduces the cost of credit - induce agents to substitute away from money towards exchange credit. The implied interest elasticity of money demand rises with the ináation rate and Önancial innovation rather than being constant as is typical in shopping time speciÖcations. Using quarterly data for the US and Australia, we Önd evidence of cointegration for the money demand model. This money demand stability results because of the extra series that capture Önancial innovation; included are robustness checks and comparison to a standard money demand speciÖcation.
Keywords: C23; E41; O42; 330